The roles of heat shock protein 70 (HSP70) and heat shock protein 90 (HSP90) in osmoregulatory and metabolic tissues of milkfish (Chanos chanos) under osmotic stress - Khotibul Umam; Cheng-Hao Tang; Tsung-Han Lee (Journal of Aquatropica Asia, 2016)
As an euryhaline fish, milkfish was able to adapt to a wide range of environmental salinity. However, to improve the survival and health of the stressed milkfish, the roles of HSPs are needed to prevent some damages caused by salinity effects. Therefore, maintenance of osmotic homeostasis is very important for milkfish. The present study investigated the HSPs expression induced by hypotonic stress in gills, kidney (osmoregulatory organ) and liver (metabolic organ) of euryhaline milkfish. Since heat shock response is a predominant cellular stress response, two of its major components, heat shock protein 70 (HSP70) and 90 (HSP90) were examined in this study. Two major hsp genes were first identified by cloned from the transcriptome database. In addition, the protein expression were examined through seawater (SW; 35‰) and freshwater (FW) acclimation experiments (> 2 weeks). At the osmoregulatory organ (gill and kidney), the expression of gill HSP90 and 70 revealed upregulation in the FW group. While, kidney HSP90 and 70 was showed no significant different between FW and SW. On the other hand, the expression of HSP90 and 70 based on relative intensities of immunoreactive bands at liver organ was similar between the FW and SW. These findings demonstrated that compared to SW environment, the FW was more stressful to milkfish osmoregulation and effected significantly to osmoregulatory organ.